The Phantom Airman - Walker, Rowland, 1876-1947 (Salt Lake City, UT : Project Gutenberg, 2013)
"The Phantom Airman" by Rowland Walker is a work of fiction written in the early 20th century. This novel, set in the post-World War I era, centers around Rittmeister Heinrich von Spitzer, a disaffected former German airman who becomes an aerial outlaw, leading a band of former pilots with aspirations of revenge against their enemies. The story explores themes of courage, ambition, and the pursuit of adventure as these characters navigate tensions between nations. At the start of the narrative, the reader is introduced to Rittmeister von Spitzer, who rallies his comrades following Germany's defeat in the war, igniting their desire to undertake a daring mission involving a secret advanced aeroplane known as the Scorpion. Amidst this backdrop of brewing rebellion, the three pilots forge a bond as they prepare to harness the power of this revolutionary flying machine. The opening portion sets a tone of urgency and excitement, laying the groundwork for a thrilling adventure filled with danger and aerial battles, as the tale unfolds against the richly imagined landscape of post-war Europe. (This is an automatically generated summary.)
Release date is 2013-07-20
Produced by Al Haines
Keywords: Science fiction; Pirates -- Juvenile fiction; Airships -- Juvenile fiction; Aeronautics -- Juvenile fiction